Trends in the Use of E-Commerce in an Axiological Review of Islamic Business Ethics - Nasihatul Ummah, Ina; Ariyanti, Vivi (Darajatuna: Interdisciplinary Journal of Islamic Studies, 2025)
E-commerce transactions, often referred to as online buying and selling, are transactions conducted by sellers and buyers over the Internet, where sellers and buyers do not meet in person. Online buying and selling have become increasingly popular because they make it easier for sellers to market their goods and for buyers in practice, there are still sellers who commit fraud. Therefore, ethics is needed in the practice of online buying and selling, ethics is a branch of philosophy that teaches ideas of good and bad, positive and negative. The type of writing in this article is a library research study using qualitative methods aimed at discussing several themes about how online buying and selling in Islamic economic business, the relationship between ethics and the branch of philosophy, the philosophical approach to Islamic business ethics from an axiological perspective, as well as the perspective of business ethics and its practice in the use of e-commerce. In this article, it can be concluded that the trend of e-commerce usage has not fully implemented Islamic business ethics, as in practice there are still shortcomings such as fraud that results in losses for one party. However, on the other hand, e-commerce always strives to apply the business ethics taught by the Prophet Muhammad SAW by avoiding practices of riba, gharar, maisir, and other harmful activities. Keywords: E-commerce, ethics, Islamic business